A coenocline of the high-ranked syntaxa of ruderal vegetation - Mucina, Ladislav; van Tongeren, O. (1989)
Two sets comprising 1419 and 1350 phytosociological relevrs of ruderal vegetation classified into 9 and 7 orders, respectively, from an area in the Podunajskh nizina Lowland, western Slovakia were ordinated using correspondence and detrended correspondence analyses. The paper describes a coenocline of the high-ranked syntaxa contained in the data sets, and discusses some issues of the classification of the syntaxa involved. The Bidentetalia and Potentillo-Polygonetalia should be considered a special category of synanthropic vegetation as habitat moisture (flooding and waterlogging) play the controlling role in the formation of structural and dynamical patterns within these communities. The latter factor complex is responsible for the clear separation of these orders from the other syntaxa included in the ordinations. The coenocline of terrestrial ruderal vegetation units has the following sequence along the CA axis 1 : Poo-Polygonetalia, Sisymbrietalia, Eragostrietalia, Onopordetalia, Agropyretalia repentis, Artemisietalia vulgaris and Glechometalia hederaceae. Various complexes of soil factors and anthropogenic disturbance are operational along the concatenation (a series of portions composing the coenocline). The factor complex includes soil compaction, trampling disturbance, nutrient status, soil texture and moisture, and solar irradiation. Step-by-step ordination and interpretation of concatenated portions of the coenocline proved to be useful in the analysis of complex data sets.